Distribution of Zakat At the Baitul Maal Foundation of Bank Rakyat Indonesia (YBM-BRI) Medan Regional Office Towards Victims of the Sinabung Eruption Disaster - Dedy Efendi (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
Islamic teachings make zakat a form of worship with social aspects to serve as a foundation for building a system that realizes the welfare of this world and the hereafter by integrating it into worship, which means giving a significant role to the belief in faith that controls a believer in his life. In distributing zakat, of course, attention must be paid to the place or location of the zakat target, namely by prioritizing domestic distribution, by conducting local distribution or prioritizing zakat recipients who are in the closest environment to where the zakat funds are collected (muzakki area) or zakat institutions compared to distribution to other areas. The many new, unexpected events, pressing needs of the community, and people who are pressed to meet their living needs are new problems in fiqh, especially zakat. One group that is pressed and in dire need of assistance are victims of natural disasters, where currently many natural disasters are affecting communities in various regions.